2005
DOI: 10.3758/bf03195302
|View full text |Cite
|
Sign up to set email alerts
|

Not the same old hindsight bias: Outcome information distorts a broad range of retrospective judgments

Abstract: The hindsight bias (e.g., Fischhoff, 1975) illustrates that outcome information can make people believe that they would have (or did) predict an outcome that they would not (or did not) actually predict. In two experiments, participants (N ϭ 226) made a prediction immediately before receiving outcome information. Therefore, participants could not distort or misremember their predictions to make them align with the outcome information. In both experiments, participants distorted their reports of how certain the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…By contrast, CGI-S only needs representation of the patient's current condition. Thus, the current results might be interpreted as suggesting that using CGI-I might be more prone to well known effects of hindsight memory distortion [e.g., [26]]: When using CGI-I at discharge, therapists, teams and patients might have been inclined to retrospectively recall the patient's condition at admission as more impaired than it really was according to CGI-S adm and thus rated change of condition as more prominent. If this was the case, in our view, it would threaten the validity of CGI-I as outcome measure in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, CGI-S only needs representation of the patient's current condition. Thus, the current results might be interpreted as suggesting that using CGI-I might be more prone to well known effects of hindsight memory distortion [e.g., [26]]: When using CGI-I at discharge, therapists, teams and patients might have been inclined to retrospectively recall the patient's condition at admission as more impaired than it really was according to CGI-S adm and thus rated change of condition as more prominent. If this was the case, in our view, it would threaten the validity of CGI-I as outcome measure in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…First, in the feedback paradigm participants cannot misremember their prior decision because feedback is administered immediately after the identification is made. Second, participants are asked to recall judgements surrounding a decision, rather than a decision itself (see Bradfield & Wells, 2005, for a fuller discussion of these issues). Therefore, the post-identification feedback effect demonstrates that outcome information can distort memories beyond the boundaries first outlined by Fischhoff.…”
mentioning
confidence: 99%
“…Whereas there is little skepticism about the ubiquity or robustness of hindsight bias, it is discussed how to taxonomize varieties of the phenomenon (Bradfield and Wells ; Blank et al. ).…”
Section: The Empirical Case For Outcome Biasmentioning
confidence: 90%
“…Whereas outcome bias concerns the evaluation of an individual or procedure responsible for the outcome, classic hindsight bias studies showed that knowledge of the outcome causes participants to overestimate its probability (Fischhoff ). This may lead people to think that they knew the outcome before it occurred—a “knew‐it‐all‐along” effect (Fischhoff and Beyth ; Bradfield and Wells ; Blank et al. ).…”
Section: The Empirical Case For Outcome Biasmentioning
confidence: 99%